40.8k views
0 votes
Let the graph of g be a vertical stretch by a factor of 3 and a reflection in the y-axis, followed by a translation 2 units left of the graph of f(x)=x^2-5x+1 . Write a rule for g .

User Tang Jiong
by
5.1k points

1 Answer

7 votes

Answer:We may rewrite f(x) = (x-1)^2

We stretch by having 3(x-1)^2

We reflect about the y axis by changing x to -x: 3(-x-1)^2 = 3(x+1)^2

We move to the left by adding 2 to x: 3(x+2+1)^2 = 3(x+3)^2

Step-by-step explanation:A way to verify this: Consider y = x^2 to be the unit parabola. f(x) = (x-1)^2 moves the unit parabola one to the right, so it is symmetric about x = 1; We then vertically stretch it by a factor of 3; reflection about the y-axis moves the parabola to be symmetric about x = -1; moving to the left by 2 means the parabola is now symmetric about x = -3; thus, we have a stretched unit parabola symmetric about x = -3, so g(x) = 3(x+3)^2

We may write g(x) = 3x^2 + 18x + 27, also.

User Sampad
by
5.0k points